The Mediating Role Of Total Quality Management In Relationship Between The Operations Management- Productivity And Long-Run Survival Of The Firm (Journal of Pharmaceutical Negative Results, 2023)
Aim/Purpose:- The aim of the descriptive research study was to know the mediating role of Total Quality Management in relationship between the operations management and long-run survival of the firm. The list of TQM practices may show better results to enhance the productivity of the organization. Outcome:- The outcome of the research model may be witnessed with respect to direct and in-direct effect. The mediating variables will give better results as the continuous assessment, strategic plan, process centered, decision-making, systematic approach, employee safety, customer focused and other factors will give better results with respect to the dependent variable productivity-customer satisfaction and long-run survival of the firm. Research Methodology/Design/Approach:- The model can be better understood by taking the advantage of primary data sources by applying the descriptive and inferential statistics with the help of goodness of fit index measures like: GFI, AGFI, NFI, TLI, CFI should be >.90 and the RMSEA <.08. Generalizability:- The outcome of the research can be generalized under any phenomenon where need arises to assess the productivity of the organization with the help of total quality management practices.